Participatory Governance of Culture and Cultural Heritage: Policy, Legal, Economic Insights From Italy - Iaione, Christian; De Nictolis, Elena; Santagati, Maria Elena (Frontiers in Sustainable Cities, 2022)
The topic of participatory governance of cultural heritage (hereinafter PGCH) is increasingly at the core of the debate on the policy approach to cultural heritage in Europe. This paper aims at offering an innovative approach to this topic by bringing a multi-actor, commons-based governance model, whereby it is often stated that PGCH may well be implemented by entrusting local communities with the restoration and valorization of cultural heritage. We argue that this model is best realized through a public-private-community partnership (PPCP) employing a diversity of legal tools. The article sketches out the legal background underpinning PGCH, provides an overview of its conceptualization in the academic debate and looks at the main policy initiatives adopted at the European and Italian domestic level. The article goes on focusing on commons-oriented case-studies of PGCH, adopting a qualitative methodology: the experimental process of the Co-Roma social partnership (Rome); the Faro Heritage Community Friends of Molo San Vincenzo (Naples); the Royal Estate of Carditello (San Tammaro); the Catacombs in Rione Sanità (Naples). Finally, the article raises some reflections and comments on the peculiarity of the PPCP model and its criticalities. The main argument we advance is that a commons-inspired, multi-actor governance model is a way to implement the vision entrenched by the European Union and the Council of Europe for supporting PGCH. This approach to PGCH may contribute to develop a sustainable and inclusive governance model, adaptive to local needs.